PENGARUH KOMITE AUDIT, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2015 – 2017) - Nureini Rifti Widyaningsih, Fadjar Harimurti & Bambang Widarno (Universitas Slamet Riyadi, 2019)
The purpose of this research was: 1) analyzes the significance of the influence of the audit Committee against tax evasion on banking company listed on the Indonesia stock exchange Years 2015 - 2017. 2) analyzes the significance of the influence of the size of the company against tax evasion on banking company listed on the Indonesia stock exchange Years 2015 - 2017. 3) Analyzing the significance of the influence of leverage against tax evasion on banking company listed on the Indonesia stock exchange Years 2015 - 2017. The research results obtained conclusions that: 1) the audit committee of insignificant negative effect against tax evasion on banking company listed on the Indonesia stock exchange Years 2015 - 2017. 2) size of company positive significant effect against tax evasion on banking company listed on the Indonesia stock exchange Years 2015 - 2017. 3) Leverage significant negative effect against tax evasion on banking company listed on the Indonesia stock exchange Years 2015 - 2017. Keywords: audit committee, the company's size, leverage, tax evasion